2014
DOI: 10.1891/2156-5287.4.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Considering a Relational Model for Depression in Women With Postpartum Depression

Abstract: Purpose To extend testing of a relational theory that a low sense of belonging, delayed or impaired bonding, and loneliness are salient risk factors for postpartum depression (PPD) in women. Methods Data for this theory-testing analysis came from a larger prospective longitudinal cohort study and included women who were retained to the end of the study at the 6 week postpartum interview (n=564). Structural equation modeling was used to test the “fit” of the model and determine significance of direct and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…It can thus be concluded that the participants situated depression within the relational domain. A recent study by Lourens and Kruger (2013) conducted in the same community with adult women also found depressed participants to situate their causes and experiences of depression within the relational domain, suggesting the appropriateness of a relational model of depression (Kruse, 2012;Kruse, Williams & Seng, 2014;Lund, Chan & Liang, 2014). Situating depression within the relational domain may hold implications for therapy: situating the cause and existence of depression within the relational domain means that treatment should address this domain.…”
Section: Resultsmentioning
confidence: 95%
“…It can thus be concluded that the participants situated depression within the relational domain. A recent study by Lourens and Kruger (2013) conducted in the same community with adult women also found depressed participants to situate their causes and experiences of depression within the relational domain, suggesting the appropriateness of a relational model of depression (Kruse, 2012;Kruse, Williams & Seng, 2014;Lund, Chan & Liang, 2014). Situating depression within the relational domain may hold implications for therapy: situating the cause and existence of depression within the relational domain means that treatment should address this domain.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, mother and their family members should be educated about problems that they might encounter during the postpartum period, the symptoms of PPD, and where to apply for help when needed. Because, low perceived social support from a healthcare practitioner is reported as a predictor for PPD, supportive relationships with nurses, especially for women at risk of depression, could increase women's sense of control and well‐being and, ultimately, prevent PPD.…”
Section: Discussionmentioning
confidence: 99%
“…PPD is a debilitating disorder that can affect not only maternal function and overall health but also the health of the infant and the entire family . The negative effects of PPD include poor self‐care, malnutrition, noncompliance with prenatal care, higher rates of tobacco and alcohol use, pregnancy‐related complications such as early gestational age at birth and low birth weight, impaired mother‐infant attachment, lower rates of breastfeeding, marital discord, and poor parenting .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is conflicting evidence for the association in the community [76,77,78,79,80,81,82,83]. An association could be due to cause or effect [84] or both. Depression and impaired ‘bonding' often have a different severity and timing, and a different response to treatment [85,86,87,88,89].…”
Section: Definitionmentioning
confidence: 99%